Solid waste management: Belo Horizonte’s study case - Ferreira, Evaldo de Melo; Barros, Raphael Tobias de Vasconcelos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
The main objective of this study is to present the instruments related to solid waste in Brazil, specifically in the city of Belo Horizonte, as well as to characterize the aspects of waste management abroad. In addition to websites of different governments, scientific databases were consulted, among them are: SciELO, Science Direct and Web of Science. Although having a major regulatory framework on the management of solid waste, and that the Law 12.305 of August 2010, Brazil is lagging when it comes to the application of what is regulated. In 2015, it was decided to extend the deadline for municipalities to close their dumpsters and then use landfills, which was not fulfilled. Thus, it was decided to extend the deadline, share that view by different scholars as an error. During this study, it was observed that among the major flaws in the Brazilian management model, is meeting deadlines established by law, which differs from the model adopted in Europe, after the deadline, fines are levied on the waste generator that does not comply with the provisions. Unfortunately, in Brazil, solid waste management by the government is still seen in the wrong way, for something interesting to remember is that with a good waste management, spending vector control (and therefore healthy) will be considerably reduced.The main objective of this study is to present the instruments related to solid waste in Brazil, specifically in the city of Belo Horizonte, as well as to characterize the aspects of waste management abroad. In addition to websites of different governments, scientific databases were consulted, among them are: SciELO, Science Direct and Web of Science. Although having a major regulatory framework on the management of solid waste, and that the Law 12.305 of August 2010, Brazil is lagging when it comes to the application of what is regulated. In 2015, it was decided to extend the deadline for municipalities to close their dumpsters and then use landfills, which was not fulfilled. Thus, it was decided to extend the deadline, share that view by different scholars as an error. During this study, it was observed that among the major flaws in the Brazilian management model, is meeting deadlines established by law, which differs from the model adopted in Europe, after the deadline, fines are levied on the waste generator that does not comply with the provisions. Unfortunately, in Brazil, solid waste management by the government is still seen in the wrong way, for something interesting to remember is that with a good waste management, spending vector control (and therefore healthy) will be considerably reduced.